Renal papillary necrosis - Stephen A. Geller; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2013)
In 1877, Dr. Nikolaus Friedreich (1825-1882; student of Virchow who became Professor of Pathology at Heidelberg and who also described Friedreich's ataxia) first described renal papillary necrosis (RPN) in patients with prostatic hypertrophy and secondary hydronephrosis. Thereafter in 1937, Froboese and Günther emphasized the association of this entity with diabetes mellitus. These authors also observed renal papillary necrosis in cases of urinary tract obstruction even in the absence of diabetes mellitus.